GC.MS Analysis of Pumpkin Seeds (Cucurbita maxima, Cucurbitaceae) - Elhassan, M. Abdalla; Hoyam, H. S. Ahmed; Samia, H. Abdalrahman; Salwa, M. E. Khogali (Archives of Business Research, 2018)
The present study was conducted to confirm the traditional uses of pumpkin plant in the treatment of many ailments on scientific basis. Pumpkin seeds , also known as pepitas , are small. Flat. whitish green in colour . Most pumpkin seeds are encased in tan or soft white testa. Seeds were purchaced from Khartoum local market , then dried in shade and powdered. Active constituents were extracted in soxhlet ,s apparatus using petroleum ether ,chloroform and ethanol in successive manner. Each extract was dried reserved in refrigerator for further investigations.. GC-Ms analysis for pumpkin seeds extract , and the structure activity relationship and correlation between the detected active constituents were don e Phytochemical screening was carried out for